Strategi Pendidikan Karakter Peduli Lingkungan: Sebagai Madrasah Educotourism - Muhsin, Moh. Ali; Ifadhah, Hurriyatul (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
Character is the most basic thing that is embedded in students including morals, ethics, and morals owned by students. So that with a character education strategy that cares about the environment, it can make quality students. MTsN 3 Pamekasan is an educotourism madrasa that has a strategic program that is sustainable in providing character education that cares about the environment for its students. This research was conducted by collecting data through interviews and conducting a SWOT analysis of the results obtained. The design of character education is based on the vision of character education implemented by environmental madrasas which upload, encourage, which makes it easier for a person to develop good habits in everyday life, habits that arise based on awareness, belief, sensitivity, and attitudes in several forms including namely in the development of Green Open Space, school culture. The implementation of environmental care character education programs can be carried out by providing healthy canteen services, garbage banks, clean Fridays and tree planting through these services can shape students' character of environmental care and will avoid environmental damage. Evaluation in the character education program cares for the environment by holding meetings every week, month and once every semester which involves the head of the madrasa, and all teachers.